Non-24-hour sleep–wake syndrome improved by low-dose valproic acid: a case report - Kurita M; Moriya T; Nishino S; Hirata E; Hirasawa N; Okubo Y; Sato T (Neuropsychiatric Disease and Treatment)
Masatake Kurita,1–3 Takahiro Moriya,2 Satoshi Nishino,2,4 Eishin Hirata,4 Noriyasu Hirasawa,5 Yoshiro Okubo,3 Tadahiro Sato4 1Wakamiya Hospital, Koutokukai, Yoshihara, Yamagata, 2Department of Cellular Signaling, Graduate School of Pharmaceutical Sciences, Tohoku University, Sendai, Miyagi, 3Department of Psychiatry and Behavioral Science, Graduate School of Medicine, Nippon Medical School, Sendagi, Tokyo, 4Sato Hospital, Koutokukai, Kunugizuka, Nanyo, Yamagata, 5Laboratory of Pharmacotherapy of Life-Style Related Diseases, Graduate School of Pharmaceutical Sciences, Tohoku University, Sendai, Miyagi, Japan Abstract: A woman was diagnosed with non-24-hour sleep–wake syndrome and depressive symptoms. Her depressive symptoms did not respond to standard doses of several antidepressants or mood stabilizers. Furthermore, her sleep–wake cycle remained non-entrained despite treatment with a melatonin-related drug, vitamin B12, and phototherapy. Ultimately, her sleep–wake rhythm was restored to a 24-hour pattern with a low dose of valproic acid, and her depressive symptoms tended to improve as a result of synchronization without antidepressants. Low-dose valproic acid appears to be one of the effective means of entraining circadian rhythms in patients with non-24-hour sleep–wake syndrome, which in turn likely improves associated depressive symptoms. Keywords: circadian rhythm sleep disorder, mood stabilizers, vitamin B12, melatonin, phototherapy, antidepressants, depression